Film‐Depth‐Dependent Light Reflection Spectroscopy for Photovoltaics and Transistors. Issue 22 (24th October 2021) - Shen, Zichao; Jiang, Yihang; Yu, Jinde; Zhu, Yuanwei; Bu, Laju; Lu, Guanghao
Abstract: Organic thin films are widely investigated for solar cells, field‐effect transistors, and other thin film devices. However, rare methods are available to characterize the film‐depth dependent variations of materials. Here, a film‐depth‐dependent light reflection spectroscopy of polymer thin films is proposed to sequentially show the optical properties at each film‐depth and consequently characterize the vertical phase segregation of polymer thin films, which is applicable for both transparent and opaque systems. Synchronic acquirement of light reflection and transmission spectra during soft plasma etching optimizes the film‐depth profiling resolution toward 1 nm, which is applied to organic solar cells and organic field‐effect transistors characterizations. Abstract : Organic semiconductors are widely used in organic electronics; however, rare methods are able to characterize the film‐depth dependent structure. Synchronic acquirement of transmission spectra during soft plasma etching is an efficient method to characterize the film‐depth dependent structure; whereas the strong reflection limits the resolution. Introducing reflection spectroscopy into characterization optimizes the film‐depth resolution toward 1 nm.